2019
DOI: 10.1039/c9dt03553b
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional materials based on the double-perovskite organic–inorganic hybrid (CH3NH3)2[KCr(CN)6] showing switchable dielectric, magnetic, and semiconducting behaviour

Abstract: Herein, we have synthesised and characterised a novel organic–inorganic hybrid crystal, [CH3NH3]2KCr(CN)6 (MACr).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 51 publications
1
34
0
Order By: Relevance
“…Another point worth commenting on is that the phase transition temperature from the cubic disordered phase is much lower for Pyr 2 KCr(CN) 6 (237.8 K on cooling) than for its MA analogue (447 K). 39 A study of double perovskite cyanides comprising MA + cations showed that the phase transition temperature decreases with an increasing TF, and the cubic phase would be stable below 298 K when the TF > 0.873. 68 Therefore, the large increase in the phase transition temperature when going from Pyr 2 KCr(CN) 6 to MA 2 KCr(CN) 6 can be attributed to the large decrease in the TF for the latter compound (the TF of MA 2 KCr(CN) 6 is 0.825).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another point worth commenting on is that the phase transition temperature from the cubic disordered phase is much lower for Pyr 2 KCr(CN) 6 (237.8 K on cooling) than for its MA analogue (447 K). 39 A study of double perovskite cyanides comprising MA + cations showed that the phase transition temperature decreases with an increasing TF, and the cubic phase would be stable below 298 K when the TF > 0.873. 68 Therefore, the large increase in the phase transition temperature when going from Pyr 2 KCr(CN) 6 to MA 2 KCr(CN) 6 can be attributed to the large decrease in the TF for the latter compound (the TF of MA 2 KCr(CN) 6 is 0.825).…”
Section: Resultsmentioning
confidence: 99%
“… 3 , 36 38 In that context, the most promising family of 3D switchable perovskites constitutes cyanides of the general formula A 2 M I M III (CN) 6 (A = organic cation; M I = Na, K, or Rb; M III = Co, Fe, or Cr). A step-like change of dielectric permittivity was reported for a few cobalt 39 − 45 and iron 42 , 43 , 46 , 47 cyanides, but a reversible change between on and off states by a thermal stimulus was demonstrated only for cobalt analogues comprising methylammonium (MA + ) and iron analogues comprising MA + and dimethylammonium (DMA + ) cations. 39 , 47 It is worth noting that we have discovered switchable properties controlled by temperature also for a nonperovskite cobalt cyanide network comprising pyrrolidinium (Pyr + ) cations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the process of phase transition, the latent heat of phase transition is absorbed or released. Among them, dielectric phase transition materials can switch the dielectric constant between low dielectric state and high dielectric state under the stimulation of external temperature, and have potential applications in the fields of information storage, sensors, signal processing and storage equipment [23–35] . In the past few years, they have received great attention and became a hotspot of multifunctional materials research.…”
Section: Introductionmentioning
confidence: 99%
“…Switchable dielectric materials, which usually exhibit a reversible dielectric transition between low‐ and high‐dielectric states under external stimuli, have attracted increasing attention due to they possess rich potential applications in the field of smart electrical and electronic devices [1–5] . From the microscopic viewpoint, the dipolar motions such as molecular rotations contributes greatly to dielectric constant in hybrid organic‐inorganic materials, compared with the electronic and ionic displacements [6–9] .…”
Section: Introductionmentioning
confidence: 99%